Prognostic value of microsatellite instability and p53 expression in metastatic colorectal cancer treated with oxaliplatin and fluoropyrimidine-based chemotherapy - Nöpel-Dünnebacke, S.; Schulmann, K.; Reinacher-Schick, A.; Porschen, R.; Schmiegel, W.; Tannapfel, A.; Graeven, U. (Zeitschrift für Gastroenterologie, 2014)
Purpose: The aim of this study was to evaluate the prognostic value of MSI-H and p53 overexpression in metastatic colorectal cancer (mCRC) treated with oxaliplatin and fluoropyrimidine-based first line chemotherapy. Methods: Tumour samples were retrospectively obtained from 229 patients from a prospective randomised phase III trial of the AIO colorectal study group, comparing CAPOX and FUFOX in mCRC. Immunohistochemistry of p53 and MMR proteins as well as microsatellite analysis were performed. Results: The incidence of MSI-H and p53 overexpression was 7.9 % and 65.4 %, respectively. MSI-H status was not correlated with ORR, PFS and OS. We observed a trend to lower DCR for MSI-H tumours (65 % vs. 85 %, p = 0.055). p53 overexpression was not correlated with DCR, ORR and PFS. The median OS of patients with tumors with p53 overexpression was significantly longer compared to tumors withhout p53 overexpression (19.6 vs. 15.8 months; p = 0.05). The post-progression survival (PPS) of p53-positive patients undergoing 2nd and/or 3rd line chemotherapy with irinotecan and/or cetuximab was significantly longer compared to p53-negative patients.Conclusion: MSI-H tumours tend to have lower disease control rates when treated with an oxaliplatin/fluoropyrmidin combination. mCRC patients with p53 overexpression undergoing an irinotecan containing second- or third-line chemotherapy after oxaliplatin failure have a significantly longer post-progression survival compared to patients without p53 overexpression. To validate the clinical impact of p53 in patients with mCRC treated with irinotecan- and/or cetuximab further studies are needed.
Keywords: metastasierters kolorektales Karzinom; Mikrosatelliteninstabilität; p53; Oxaliplatin; Prognose